Digital marketing strategies of Ogilvy & Mather Communications (Pvt.) Limited - Saikat, Md. Zobaidul Islam (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.